1990
DOI: 10.1103/physreva.41.283
|View full text |Cite
|
Sign up to set email alerts
|

MolecularK-shell photoionization cross sections in the relaxed-core Hartree-Fock approximation

Abstract: The relaxed-core Hartree-Fock (RCHF) approach to the calculation of E-shell photoionization cross sections is analyzed and applied to I(-shell single-hole ionization in CO. A direct method based on the Schwinger variational principle and single-center-expansion techniques is used to generate the continuum orbitals associated with the motion of the photoelectron in the direct and exchange potential of the relaxed ion. A method is presented for evaluating the ¹lectron transition moment, a step that has posed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 31 publications
5
42
1
Order By: Relevance
“…For example, in C 1s photoionization of neutral CO 2 , the cross sections computed using the ion molecular orbitals or averaged (Slater's transition-state [33]) orbitals give much better agreement with experimental observations than those obtained with CO 2 molecular orbitals [34][35][36]. Slater's transition-state orbitals have been used extensively in core-level photoionization studies and have been shown to give results consistent with experimental measurements [34,35,37,38]. To investigate the orbital relaxation effects in the case of photodetachment, here we compute the cross sections using anion, neutral and Slater's transition-state orbitals.…”
Section: A Photodetachment Cross Sectionssupporting
confidence: 51%
“…For example, in C 1s photoionization of neutral CO 2 , the cross sections computed using the ion molecular orbitals or averaged (Slater's transition-state [33]) orbitals give much better agreement with experimental observations than those obtained with CO 2 molecular orbitals [34][35][36]. Slater's transition-state orbitals have been used extensively in core-level photoionization studies and have been shown to give results consistent with experimental measurements [34,35,37,38]. To investigate the orbital relaxation effects in the case of photodetachment, here we compute the cross sections using anion, neutral and Slater's transition-state orbitals.…”
Section: A Photodetachment Cross Sectionssupporting
confidence: 51%
“…At higher energies the RCHF approximation has also been used (CO 43,44,50,52,54,67,[115][116][117][118][119][120] , N 2 3 ). This is in contrast with the frozen core Hartree Fock (FCHF) approximation, which has widely been used in most earlier and some recent works (CO 42,48,58,74,75,106,121 , N 2 22,27,32,58,74,75,106 ).…”
Section: Theoretical Methods Within the Fixed-nuclei Approximationmentioning
confidence: 90%
“…Another single channel approach is the Stieltjes-Tchebycheff moment theory (STMT) (CO 47,101 ; N 2 10,30,101,102 ) which is able to describe shape resonances near the ionization threshold (see results below) but suffers from limited energy resolution and range. The Schwinger iterative approach that has been implemented at the frozen core (FCHF) 32,46,48 and relaxed core (RCHF) 14,42,[103][104][105][106] levels for polyatomic molecules can instead produce accurate solutions of the molecular electronic continuum. Another method that has been shown to provide accurate results for large systems is the present multicenter Bspline static-exchange DFT method 17,24,33,49,107 , which makes use of the Kohn-Sham density functional theory to describe the molecular ionic states and the Galerkin approach to evaluate the continuum electron wave function in the field of the corresponding Kohn-Sham density.…”
Section: Theoretical Methods Within the Fixed-nuclei Approximationmentioning
confidence: 99%
See 2 more Smart Citations